EFEKTIFITAS MUSYAWARAH GURU MATA PELAJARAN (MGMP) GURU PENDIDIKAN AGAMA ISLAM - Muhammad Hasyim (LP3M IAI Al-Qolam Malang, 2015)
Teachers are one of the most important components in the educational process. They will determine the success of education because they design, manage, implement and evaluate the learning process. Not only that, they also have a considerable influence on changes in behavior and the development of students. Therefore, teachers are required to always improve their quality of competence and professionalism. Many ways have been being taken by the government to boost the quality of education in junior/senior high school. One of them is MGMP (Subject Teachers Forum). Teachers join MGMP, Including PAI (Islamic Lessons)teachers, are expected to increase the professionalism so as to improve the quality of education. MGMP is a professional communication network that can be utilized by the teachers in developing their professionalism by discussing and practicing the preparation of the annual program (prota), the semester program (promes), the analysis of the subject matter, teachingunitprogram, learning methods, evaluation tools, teaching materials, teaching media utilization and others. Keywords: MGMP, teachers, learning process